Pengukuran tingkat penerimaan konsumen pada zero waste store menggunakan pendekatan sustainable marketing - Novita Erma Kristanti; Farah Tiara Hanun; Bayu Arga Putra Pratama; Makhmudun Ainuri; Suharno Suharno (AGROINTEK, 2025)
Indonesia is second on the list of countries contributing the most plastic waste globally, after China. This condition occurs because of the high number of household demands for FMCG (fast-moving consumer goods) products, most of which are packaged using plastic. Society needs action to reduce plastic waste. Sustainable marketing is a socially and environmentally responsible marketing principle that meets the needs of today's consumers and businesses. Sustainable marketing also preserves and ensures that future generations can meet their needs. This approach aims to positively impact the environment in a sustainable marketing scheme in Indonesia. This research aims to measure consumer acceptance of zero-waste stores and prioritize optimal business activities based on sustainable marketing. Collecting respondent data used a mixed method and a purposive sampling method. Data collection uses questionnaires for consumers and in-depth interviews with related parties, namely, the government, academics, and business managers. Research data processing uses the CSI (customer satisfaction index) method to measure consumer acceptance. Data analysis was carried out based on sustainable marketing attributes. The object of this research is zero-waste shops in Yogyakarta, namely Peony Ecohouse and Vert Terre. The research results show that consumer acceptance falls into the criteria of satisfaction with zero-waste store activities. Zero-waste store activities with sustainable marketing based on customer-oriented marketing (C-OM) and customer-value marketing (C-VM) assessments show positive values, meaning that activities in zero-waste stores directly impact consumers. The recommended business activity priorities are promoting and strengthening information regarding environmentally friendly zero-waste stores through direct events and social media, maintaining product price stability, maintaining continuous product availability,  and providing quality products.